Investigations on blood physiology, tissues histology and gene expression profile of Fusarium oxysporum challenged fish - Pervaiz, Sumaira; Kanwal, Zakia; Manzoor, Farkhanda; Tayyeb, Asima; Akram, Qaiser (Penerbit Universiti Kebangsaan Malaysia, 2022)
Labeo rohita was challenged with Fusarium oxysporum to demonstrate a thorough immune response. Significant alterations in hematological parameters viz; erythrocyte, hemoglobin, hematocrit, mean corpuscular hemoglobin concentration, mean corpuscular volume, packed cell volume, platelets, and leukocytes were observed. Total serum protein, albumin, globulin, A/G ratio, aspartate aminotransferase, alkaline aminotransferase, alkaline phosphatase activity, and cholesterol were also altered in the infected fish. Marked histopathological lesions in gills, liver, and kidney (fusion of gill lamella, necrosis, edema, vacuolization, glomerulus congestion, dilated bowman’s space and renal tubules alterations) were recorded. Tissue specific gene expression data showed that interleukin was upregulated in infected fish gills, liver, and kidney but was downregulated in blood. Tumor necrosis factor-α expression was upregulated in blood, liver, and kidney and was downregulated in gills. Upregulation of interferon-γ was observed in blood, gills, and kidney but downregulated in liver. All the cellular and molecular findings from this study can be taken as critical biomarkers in the advancement of diagnostic techniques against fungal infections as a part of wide-ranging programs of systematic and comprehensive monitoring of fish health and immune system.